ASSESSING THE TEACHING INTERNSHIP PERFORMANCE OF CLASS 2024 ENGLISHPRE-SERVICE TEACHERS - Christian Loid Valenzuela; Guiller T. Marila; Marko L. Aratea (International Journal of Teaching and Learning, 2026)
The present study aimed to assess the teaching internship performance of English Pre-Service Teachers from the Class of 2024, with regard to their professionalism, classroom management, content understanding, and reflective practices. In a quantitative-descriptive research design, data was collected through a researcher-developed 4-point Likert scale answered by supervising teachers. Findings revealed that the strength of the English Pre-Service Teachers lies in professionalism, with high regard for ethics; able to communicate and deliver the lesson well, creating good adaptation. They performed quite well in managing their classes, along with creating a worthwhile learning atmosphere. The study identified variances in development regarding enhancing diversity in instructional strategies, adjusting the pace of lessons to accommodate students' learning ability, and infusing students' cultural knowledge into the curriculum. These findings highlight increasing needs for better flexibility of instruction to meet the complex demands of diverse learners' needs. The study confirms that the strengths the English Pre-Service Teachers possess regarding major teaching competencies are to be further developed in relation to differentiated instruction, integration of technology, and reflective thinking. Recommendations include continuous professional development and robust mentorship programs to support their growth, ensuring their readiness to meet the complexities of modern education.